KANDUNGAN GIZI ROTI TAWAR BENGKUANG (Pachyrhizus erosus) - Trisna Ratna Sari; Albiner Siagian; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The high consumption of white bread increased the need of wheat flour as the main ingredient of bread. The flour from wheat still can’t be cultivated in Indonesia. Bread with non-wheat flour, used the other commodities the raw material, yam that still limited as food and just a little in food industries. The technological based utilization of yam that already exist is yam flour. The purpose of this study is to know the nutrient that contained in yam white bread. This study was experimental study. The method that used for testing the nutrient content is the oven method (water and ash), micro-kjeldahl (protein content), sooxhlet (fat), luff schoroll (carbohydrate) and the gravimetric method (crude fiber content). Tests conducted in the laboratory of nutrients Palm Research Center. Based on the test results on the nutritional value of yam white bread (40% yam flour and 60% wheat flour) amounting to 33,37% water, 2,34% ash, 11,98% protein, 11,60% fat, 67,67% carbohydrate and 3,42% crude fiber. The energy content contained on yam white bread amounting to 423 kcal. Yam white bread can be used for the alternative food as the prevention of degenerative diseases. However the food portion of the yam white bread should still be considered because yam white bread high in fat. Keyword: Nutrient Content, Yam Flour, Yam White Bread